From a Distance — the Remote Cityscape as Dream and Nightmare - John EDMONDSON (E-REA)
The relationship between the individual and the city changes significantly when the city is contemplated from a distance rather than encountered from within. The remote cityscape or urban skyline induces a vision or an alternative reality that sometimes conflicts with and sometimes is an intensification of the reality of engagement with the city at close quarters. The remote cityscape thus enables and becomes a re-imagining of the city and, in so doing, bears some affinity to Baudrillard’s notion of the simulacrum and to the “true simulacrum” of the panorama as described in the “Panoramas” Convolute of Benjamin’s Arcades Project. In its remote perspective, the cityscape, like Jasper’s drug-induced vision of Cloisterham at the beginning of Edwin Drood, variously stimulates and simulates the fears, hopes, desires and ambitions of the onlooker. In the alternative or intensified reality it evokes, it may threaten or quiet, it may be bewildering or controllable. It becomes in this way a dream of the city—divorced from the physical reality from which it is constructed. The discussion focuses on Dickens’s novels, but reference is also made to work by Kingsley Amis, Chagall, Isaac Cruikshank, Grandville, Laisné, Gaskell and Hardy, and to the film The Third Man.